Alfred the Raider: Capitalizing on the Warrior-King Relationship, Morale, and Reputation to Become the Greatest Anglo-Saxon King - Nissen, Benton (URJ-UCCS: Undergraduate Research Journal at UCCS, 2021)
Despite the vast research on Alfred the Great’s Viking Wars, many historians fail to acknowledge the Germanic warrior-king relationship that defined the Anglo-Saxon Age, and how instrumental this relationship was to King Alfred’s success. This warrior-king relationship seems to be overlooked for the more exciting stories of blood and gore that overshadow the accomplishments and failures of ninth-century leaders. In the case of Alfred the Great, his achievements as a great military leader did not begin until nearly seven years after he became king, and the triumphs and failures of his earlier reign find their roots in the influence of the warrior-king relationship within Wessex. This research will define what this relationship meant to the kingship in Wessex, and stress how necessary this relationship was in creating shifts in morale between the two opposing armies, as well as Alfred’s subsequent success against Guthrum and his Great Summer Army at Edington in 878.